Water quality status in different aquatic environments in Thi- Qar province based on NSF-WQI - Afaq T. Farhood (University of Thi-Qar Journal of Science, 2019)
The present study was conducted during the period Winter &Summer of 2016 in different aquatic environments in Thi-Qar province to determine water quality status based NSF-WQI and some Iraqi & international standards. Three stations were chosen e to achieve the study, (each station consist from two sites), station (1) Euphrates River, station (2) Al-Gharraf River, station (3) Al- Chibayish Marshes.       The study result water quality conditions have been classified as (medium – good) at (NSF-WQI), some factors (physical chemical properties ) was within of the some Iraqi  & international standards. Euphrates River recorded highest pollution in compare: with Al- Gharraf River and Al- Chibayish Marshes, thus the (NSF - WQI ) is considered a good , easy and efficient way to use guide to assess the quality of the water , can us adoption on it to assess various aquatic environments.